The current role and perceived benefits and barriers of secondary care pharmacists facilitating patient participation in Clinical Trials of Investigational Medicinal Products (CTIMPs) conducted within the NHS: A cross‐sectional survey. Issue 1 (28th January 2019) - Watson, Michelle; Bewick, Bridgette M.; Tharmanathan, Puvan
Abstract: Rationale, aims, and objectives: Secondary care pharmacists are well positioned within the healthcare system to communicate with patients and provide guidance and advice regarding drug treatments. They are able to broaden the opportunities to raise the profile of Clinical Trials of Investigational Medicinal Products (CTIMPs) and positively influence research. This research aimed to investigate the perceived benefits and barriers of secondary care pharmacists being involved in CTIMPs, their current role, and the perceived benefits and barriers of developing their role in facilitating patient participation for CTIMPs (eg, by identifying or recruiting potential participants). Methods: A cross‐sectional quantitative online survey circulated to pharmacy professionals within the UK. Results: Involvement in CTIMPs and the facilitation of patient participation offered several benefits including improved communication and relationships with other healthcare professionals, developing the profession, developing training and knowledge, and exploring a personal interest. The main barriers to involvement included a lack of opportunities or awareness of opportunities, time, and funding or resources. Those employed at sites with a larger number of CTIMPs agreed more with the disadvantages; however, they also showed greater agreeance towards the benefits of pharmacy being involved in facilitating patient participation. Conclusions: Most respondents do not currently have a role in identifying or recruiting potential participants. Despite this, being involved in CTIMPs and the facilitation of patient participation was suggested to offer several benefits. Given many participants agreed there are barriers to their involvement, future research should focus on exploring organizational and individual challenges with the aim of enabling pharmacists to support recruitment activities.